Job crafting and organizational citizenship behavior: believing in your creative ability to better your job and organization - Irvin, Ryan (Kansas State University, 2017)
Working as a front line employee in the hospitality industry is not always easy. There can be long working hours, high work demand and many other disadvantages that can lead to increased stress on an employee of the industry. These disadvantages have led to one of the highest turnover rates compared to most other industries (NRA, 2017). Managers have been looking at possible ways to reduce turnover by giving employees more freedom. In most organizations, the manager implements changes in each employee’s job design and roles within the organization. Recent job design has focused on letting the employee develop some of the task they do. This certain type of job redesign is called job crafting. Job crafting is a theoretical concept where an employee is allowed to implement change or redesign certain aspects of their job (Wrzesniewski & Dutton, 2001). According to Wrzesniewski and Dutton (2001), the three main ways that one can craft their job are through changes in work tasks, relationships, and perception of one’s job. So the question is, “How does job crafting have a creative impact on front line hospitality employee behavior at work?” The purpose of this study is to examine whether job crafting is related to creative self- efficacy, which can in turn lead to employee organizational citizenship behaviors. That is, the more employees participate in crafting activities, the more they will believe that they can be creative and follow through with their creative idea, which will lead the employees to having more organization citizenship behavior. The sample for this study consists of 323 front line employees in the hotel industry. Participants’ job crafting, creative self-efficacy and organizational citizenship behaviors were measured. After running the variables through a regression analysis, the results showed a significant positive relation between job crafting and organizational citizenship behavior with creative self-efficacy as a mediator. From a theoretical perspective, this study contributes to an understanding of organizational citizenship behavior in the hotel context by shedding light on the role of job crafting. Practical implications from this study could encourage managers that are focused on improving organizational citizenship behavior in their hotels to look into promoting job crafting.
Keywords: Hotel industry; Job crafting; Creative self-efficacy; Organizational citizenship behavior